1999
DOI: 10.1038/sj.bjc.6690528
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proliferation and induction of apoptosis in soft tissue sarcoma cells by interferon-α and retinoids

Abstract: Summary Uncontrolled proliferation and a defect of apoptosis constitute crucial elements in the development and progression of tumours. Among many other biological response modifiers known to influence these mechanisms, the efficacy of retinoids and interferons in the treatment of various malignant entities is currently matter of discussion. In the present study, we have investigated the effects of 9-cis-retinoic acid (9cRA), 13-cis-retinoic acid (13cRA), all-trans-retinoic acid (tRA) and interferon-α on proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 34 publications
(32 reference statements)
1
21
0
Order By: Relevance
“…Previous experiments demonstrated that treatment with AtRA resulted in significantly decreased growth versus ethanol-treated control cells (Crouch and Helman, 1991;Brodowicz et al, 1999). We confirmed this finding in our experiment.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Previous experiments demonstrated that treatment with AtRA resulted in significantly decreased growth versus ethanol-treated control cells (Crouch and Helman, 1991;Brodowicz et al, 1999). We confirmed this finding in our experiment.…”
Section: Discussionsupporting
confidence: 82%
“…However, as cell lines inherently have resistance to pharmacologic doses of therapeutic agents, this dose was deemed appropriate for our studies. Moreover, this dose has been previously established as one that effectively inhibits RMS growth in vitro (Crouch and Helman, 1991;Brodowicz et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agent has potent effects against acute promyelocytic leukemia blast cells, and its introduction in the clinical management of the disease has dramatically changed the outcome of this historically fatal subtype of acute leukemia (5). RA and other retinoids have been shown to inhibit cell growth or to promote programmed cell death of neoplastic cells of diverse origin (7)(8)(9)(10)(11)(12)(13)(14). The molecular mechanisms that regulate the induction of the biological effects of retinoids include a series of signaling events that are initiated by the binding of retinoids to specific receptors in the nucleus of target cells.…”
Section: All-trans-retinoic Acid (Ra)mentioning
confidence: 99%
“…RA and other retinoids also induce antitumor effects by inhibiting cell growth or promoting programmed cell death of neoplastic cells of diverse cellular origin (5)(6)(7)(8)(9)(10)(11)(12). The important biological effects of RA have led to intense efforts to understand the mechanisms by which it generates its biological effects on malignant cells.…”
mentioning
confidence: 99%